2021
DOI: 10.1016/j.jece.2020.104727
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cadmium ions biosorption by fish scale from aqueous solutions using factorial design analysis and Monte Carlo simulation studies

Abstract: This work investigated cadmium ions biosorption on Fish scales (FS) of Sardina pilchardus. Different relevant parameters such as initial pH in the range 2.14 -7.76, initial cadmium concentration from 35 to 150 mg L -1 , and biosorbent dose in the range 50 -300 mg L -1 , were examined. The effect of these parameters on the cadmium removal was analyzed and optimized using full factorial design methodology and the analysis of variance. The kinetics were modelized for pseudo-second order and pseudo-first order mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Table 10 shows that interface of PS/100water/50H 3 O + /50Cl -/Collagen is more stable (Low value of ℇ Tot = -281.319 kcal mol -1 ) comparing to the PS/100water/50H 3 O + /50Cl -/HDA one (high value of ℇ Tot = -202.969 kcal mol -1 ). In addition, the negative values of E ads mean that the studied biosorption can be spontaneously shaped [31,61]. Moreover, we observed that the system of PS/100water/50H 3 O + /50Cl -/Collagen has a more negative value of ℇ ads (-94.255 kcal mol -1 ) comparing to the PS/100water/50H 3 O + /50Cl -/HDA interface (-14.631 kcal mol -1 );…”
Section: And Rdf Simulationsmentioning
confidence: 71%
See 2 more Smart Citations
“…Table 10 shows that interface of PS/100water/50H 3 O + /50Cl -/Collagen is more stable (Low value of ℇ Tot = -281.319 kcal mol -1 ) comparing to the PS/100water/50H 3 O + /50Cl -/HDA one (high value of ℇ Tot = -202.969 kcal mol -1 ). In addition, the negative values of E ads mean that the studied biosorption can be spontaneously shaped [31,61]. Moreover, we observed that the system of PS/100water/50H 3 O + /50Cl -/Collagen has a more negative value of ℇ ads (-94.255 kcal mol -1 ) comparing to the PS/100water/50H 3 O + /50Cl -/HDA interface (-14.631 kcal mol -1 );…”
Section: And Rdf Simulationsmentioning
confidence: 71%
“…The RDF is used as a technique to predict the nature of biosorption between PS and surface. The appearance of peaks from 1.00 Å to 3.50 Å is a sign of chemisorption interaction nature [31]. The stable biosorption configuration of the studied interfaces (PS/100water/50H 3 O + /50Cl -/Collagen or HDA) (Fig.…”
Section: And Rdf Simulationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Biosorbents are quite omnipresent in our environment and can be of microbial origin such as whole cell bacteria, fungi or algae and cell wall saccharide materials derived from them [11][12][13][14][15][16] . Other biological materials of phytological and zoological origin such as whole plant biomass, stem powder, grape pomace, rose wastes, peat [17][18][19][20][21][22] . Among all the biological adsorbents used in the remediation process, living microbial cells are quite effective in removing cadmium like toxicants from contaminated water bodies 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Biosorbents are quite omnipresent in our environment and can be of microbial origin such as whole cell bacteria, fungi or algae and cell wall saccharide materials derived from them 21 26 . Other biological materials of phytological and zoological origin such as whole plant biomass, stem powder, grape pomace, rose wastes, peat 27 32 . Among all the biological adsorbents used in the remediation process, living microbial cells are quite effective in removing cadmium like toxicants from contaminated water bodies 17 .…”
Section: Introductionmentioning
confidence: 99%